Green Leadership in The Spotlight: A Bibliometric Analysis of Research Developments - Murdiono, Jatmiko; Hamidah, Hamidah; Sariwulan, Tuty (Program Studi S3 Ilmu Manajemen, 2024)
Global sustainability issues require organizations to carry out strategic transformation by balancing profit, people, and planet aspects. In this context, green leadership is present as a leadership style that combines environmental orientation with management practices to support green innovation, sustainable performance, and environmentally oriented human resource management. This research aimed to provide a comprehensive overview of the development of green leadership research, identify trends, research gaps, and the direction of future academic collaboration. The research method uses a quantitative approach through bibliometric analysis with secondary data from the Scopus database using the keyword